PUBLIC DEBT IN REPUBLIC OF SRPSKA - Ivic, Mladen (Journal of process management and new technologies, 2017)
The global crisis has led to the re-questioning of the justification of economic growth based on borrowing. The issue of public spending and public debt has become particularly important for small and opened economies that are not sufficiently competitive on the world market. If one such country seeks to enter the EU, the rules on the amount of total borrowing and public debt can be a significant obstacle. In recent years, Republic of Srpska has been borrowing rapidly, so in the academic community is already concerned about the possibility and price of servicing those debts. The paper gives a theoretical explanation of the public debt and the needs for borrowing, then to set out the rules on debt level limitation. In the final part, the indicators of indebtedness of Republic of Srpska were presented on the basis of the available information, with the conclusion that this is a medium-indebted country, but also a country that is very vulnerable when it comes to maintaining macroeconomic stability and regular debt servicing.